Purpose and narrative in the punisher's rhetoric exploring Rodrigo Duterte's political rhetoric during the Pilipinas debates 2016 - Segovia, Andres Karl E. (2019)
Rhetoric is one of the most fundamental aspects of politics, whether past or present, or Western or Eastern, in orientation. At the same time, democracy has been, as characterized by Schumpeter (1947), reduced to being proceduralist in nature, essentially meaning that the relationship between voters and politicians has become transactional in nature. Within the Philippine context, politics in and of itself has never been more at the forefront of societal discourse than during the time of Rodrigo Duterte?s rise to the presidency. However, what seems to be missing from the aforementioned discourse is discussion on the role of rhetoric in Philippine politics. Drawing from previous works on politics and political rhetoric, this study is an exhaustive textual analysis of the linguistic components of Rodrigo Duterte?s political rhetoric, specifically within the context of his performances during the Pilipinas 2016 Presidential Debates. The goal was to find out how political rhetoric was utilized in the said performances, and the potential meaning/s that can be drawn from the said rhetoric. The core component of the analysis was the creation of two sets of textual codes: a priori (initial, built on concepts from symbolic convergence theory) and emergent (based on the a priori), which were used to catalogue segments of Rodrigo Duterte?s speech. The analysis took two distinct approaches: analysis of individual instances of rhetoric (?codes?) in the speeches, and the relationships (nearness/adjacency, frequency, and overlaps) between the codes utilize. Within the context of the Pilipinas 2016 Presidential Debates, it became clearer that, at least linguistically, Rodrigo Duterte utilized three stages of rhetoric. The first was to create the image of ?Duterte as part of the masa?; the second creating clear distributions between the masa (including him) and the ruling elite (with implications that this includes the other candidates); and the last building on the previous two and highlighting the distinction between him and the other candidates, and in the process place voters in an either-or proposition between the two. This rhetoric, including recurring thematic/rhetorical elements, can be seen as potentially reflective of Rodrigo Duterte?s own worldview, as well as the qualities that made him attractive to his support base. It also reflects, to different degrees, the varying criticisms levelled at him during the 216 Philippine Presidential election?s campaign period, i.e. narcissistic tendencies, violence, etc.